2020
DOI: 10.5334/jors.330
|View full text |Cite
|
Sign up to set email alerts
|

Pyrad: A Real-Time Weather Radar Data Processing Framework Based on Py-ART

Abstract: Pyrad is a real-time data processing framework developed by MeteoSwiss. The framework is aimed at reading, processing and visualizing polar data from individual weather radars as well as composite Cartesian products both off-line and in real time. The processing flow is controlled by three simple configuration files. This allows the construction of reproducible data processing chains. In the off-line mode, data from multiple radars can be ingested. It is written in the Python programming language. Most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Browning, 1971) and then brought up again by Neiman et al (1993). Recently, Flaounas et al (2016) and Oertel et al (2019) confirmed the presence of convection embedded in WCBs with radar observations. Oertel et al (2020) and Oertel et al (2021) showed that WCB-embedded convection can result in locally enhanced precipitation and that diabatic heating by convection can influence the upper-level jet by the formation of PV dipole bands.…”
Section: Introductionsupporting
confidence: 60%
“…Browning, 1971) and then brought up again by Neiman et al (1993). Recently, Flaounas et al (2016) and Oertel et al (2019) confirmed the presence of convection embedded in WCBs with radar observations. Oertel et al (2020) and Oertel et al (2021) showed that WCB-embedded convection can result in locally enhanced precipitation and that diabatic heating by convection can influence the upper-level jet by the formation of PV dipole bands.…”
Section: Introductionsupporting
confidence: 60%
“…The core data processing for both campaigns was done by the MeteoSwiss in-house-developed open-source real-time weather radar data processing framework Pyrad (Figueras i Ventura et al, 2020a), which is based on the Py-ART radar toolkit (Helmus and Collis, 2016).…”
Section: Methods and Datamentioning
confidence: 99%
“…In the following part of the paper, all the horizontal reflectivity Z H measurements and retrieved RCS data obtained from PPI and RHI scans in 2019 are statistically analyzed in order to characterize the returns from the three wind turbines by using the radar data processing framework Pyrad (Figueras i Ventura et al, 2020a). Global statistics considering the median and maximum Z H and RCS are presented.…”
Section: Weather Radar and Wind Turbine Datamentioning
confidence: 99%
“…Therefore, in this study, we focused on the optimization of these three hyperparameters by using a grid search approach. Thus, a vector of possible values for each of these hyperparameters was defined and set for the grid search implementation (n_estimators = (100, 150, 200, 300, 400, 500, 600), max_features = (total number of features [13], square root of total number of features [4]), max_depth = (3,5,8,10,13,15,20)). Here, exhaustive combinations of all hyperparameters were used to build independent models (i.e., one set of hyperparameters defines one model) and to perform their evaluation (OOB score) by using a K-fold crossvalidation.…”
Section: Machine Learning Approach: Random Forestmentioning
confidence: 99%
“…Kumar et al [12] have pointed out the geometric issues of beam broadening and weakening of the signal with distance. More recently, many of these correction procedures have been integrated into comprehensive software products, such as the processing software supplied by radar manufacturers [13], national weather services [14], or community efforts such as PyRad [15] or ωradlib [16]. Nevertheless, the situation in Peru (and Ecuador) still requires customized solutions: first, because the radar systems used are quite basic instruments (single elevation, no polarization, no Doppler information) and secondly due to the specific circumstances of the region.…”
Section: Introductionmentioning
confidence: 99%